Hubungan HUBUNGAN PRIMIGRAVIDA DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM DI WILAYAH KERJA PUSKSMAS PAYUNG SEKAKI PEKANBARU 2018 - Dewinny Septalia Dale (Indra Institute Research & Publication, 2022)
Hyperemesis gravidarum is excessive nausea and vomiting that occurs early in pregnancy until 20 weeks gestation. Hyperemesis gravidarum is more common in primigravids, because primigravids have not been able to adapt to estrogen and chorionic hormones gonadotropin. Primigravida is the first times woman to be pregnant. The purpose of this study was to determine the relationship of primigravida with the incidence of hyperemesis gravidarum. This research is quantitative type with analytic design with cross sectional approach. This research was colected in april 2018. The sample this study is pregnant women, amount to 96 respondents. The sampling technique used is accidental side. The study was conducted using primary data obtained from checklists, and univariate and bivariate analyzes using chi-square statistical test. From the analysis results obtained 50 respondents (52.1%) primigravida pregnant women, 43 respondents (44.8%) hami mother experiencing hyperemesis gravidarum. Chi-square test results obtained p value <0.05 which results 0.04. So it can be concluded that statistically there is a relationship between primigravida with hyperemesis gravidarum. The research results expected for international Midwifery can provide information through counseling and motivation to pregnant women cause the occurrence of hyperemesis gravidarum.